Analisis Penerapan Software SAP Terhadap Kinerja Karyawan Di PTPN IV Regional III Kebun Air Molek – 1 - Citra Sukma Dwika, Galuh; Nurbaiti, Nurbaiti (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
With the growth of the times greatly affecting information technology, so companies must understand and be quick in taking action. Therefore, companies must also be more innovative by changing the way they work and adjusting to the rapid growth of information technology systems. With the development of the times that continues to grow, the role of information technology is growing, especially for users to simplify their work by utilising the technology. The use of a system that is suitable for the times will now provide benefits for employees because it can increase creativity, improve employee performance and improve the quality of the company's work so that the management of the company's system development can be carried out more efficiently and effectively.Information systems that are processed simply, systemized and tight can be used by users better, especially about personal information. In the information system there is software called SAP (System Application and Product) which is owned by the ERP (Enterprise Resource Planning) system. This study discusses the application of SAP (System Application and Product) at PT Perkebunan Nusantara IV Regional III, Kebun Air Molek - 1, and sees its effect on employee performance in the human resources section. Along with the continuous development of information technology, the business world needs to implement a system that can increase productivity and efficiency. The analysis method used in this research is descriptive qualitative analysis, where interviews, observations, literature studies and documentation are used as data collection techniques. This research shows the results that the implementation of SAP with the support of training and good online infrastructure will facilitate employee data management, increase efficiency and speed in business activities and can improve maximum employee performance.